Municipal landfill Leachate-induced testicular oxidative damage is associated with biometal accumulation and endocrine disruption in rats (2015)
Improper management of hazardous wastes adversely impacts the environment and the public health. The present study was aimed at investigating the influence of Olushosun municipal landfill leachate (OMLL) from Ojota in the Lagos State of Nigeria on testicular function by assessing the plasma concentrations of reproductive hormones, testicular biometal levels, and antioxidant levels as well as observing the histological alterations in testes and epididymides of rats after exposure to 0, 12.5, and 25 % OMLL in drinking water for 7 days. Exposure to OMLL significantly decreased the daily fluid intake, but it resulted in testicular biometal accumulation as follows: lead [cadmium[nickel[iron[copper. Acute exposure to OMLL induced oxidative stress and increased the activities of marker enzymes of testicular function but markedly decreased the circulatory concentrations of luteinizing hormone, follicle-stimulating hormone, prolactin, testosterone, thyroid-stimulating hormone, triiodothyronine, and thyroxine. Testicular and epididymal degeneration with significant decrease in sperm quality and quantity were observed in OMLL-exposed rats. Collectively, the data presented herein indicate that exposure to OMLL-induced testicular dysfunction associated with biometal accumulation and endocrine disruption in rats. If the effects can be extrapolated to humans, OMLL may present significant health implications for individuals exposed to OMLL-contaminated substances.